“I felt like it was the right thing to do”: How college students’ decisions to disclose COVID-19 diagnoses reflect privacy preferences, perceptions of stigma, and cultural norms - LaFreniere, Jenna; Bedor Hiland, Emma (Qualitative Health Communication, 2024)
Background: COVID-19 diagnoses can be difficult to share, as COVID-19 faces ongoing stigmatization. Aim: Framed by communication privacy management theory, this study examines how college students make decisions to disclose their COVID-19-positive statuses (or why they may not), and how those decisions are affected by perceptions of stigma and cultural norms. Methods: This study utilizes a qualitative, interview-based methodology with twenty undergraduate student participants. Results: Responses are analyzed for themes relating to communication privacy management, noting information control and co-ownership, boundary coordination, and forced/required disclosures. Responses demonstrate that a stigmatized view of COVID-19 has largely subsided, but still affects disclosure preferences and decisions. In addition, several cultural factors also shape beliefs about disclosure practices. Discussion: These findings illuminate how perceptions of COVID-19’s stigma and cultural norms shape college students’ notions of privacy, information control, co-ownership, and ultimately disclosure practices. Highlighting implications for how best to respond to future pandemics, the data presented herein provides an exploration of the relationship between privacy strategies, stigmatization beliefs, and cultural norms. Conclusion: This information will be useful in generating institutional, education, and public health responses to future pandemics, as findings suggest an under-theorized relationship between the areas of privacy management, stigmatization, and cultural norms.